Selecting Training-Load Measures to Explain Variability in Football Training Games - Zurutuza, Unai; Castellano, Julen; Echeazarra, Ibon; Guridi, Ibai; Casamichana, David (Frontiers in Psychology, 2020)
The purpose was to study the structure of interrelationships among external (eT) and internal (iT) training intensity metrics and how these vary depending on different game formats in soccer. The variables were collected from 16 semi-professional players in seven types of small, medium, large-sided and simulate games. eT variables were (per min): velocity peak (Vmax), total distance (TDmin) and distance covered at range lower than 60% (D<60%min), between 60 and 80% (D>60%min) and higher than 80% (D>80%min) of the maximal velocity, player load (PLmin), distance covered accelerating at the range higher 2 m·s-2 (Daccmin), and decelerating at the range lower than -2 m·s-2 (Ddecmin). iT variables were: Edwards arbitrary units (EDWmin) and time spend at range higher than 80% of the maximal heart rate (T>80%HRmin). All game formats were represented by three principal components (PC), explaining from 66.9 to 76.0% of the variance. The structure of interrelationships among variables involved similar distribution in the PC that are related to energetic production systems, such as strength/neuromuscular (PLmin and/or Daccmin and Ddecmin, complemented with DTmin and D<60%min), endurance/cardiovascular (EDWmin) and velocity/locomotors (Vmax, D>60%min or D>80%min). A particular combination of external and internal intensity measures is required to describe training load of game formats.